Abstract expressionism and its relationship to visual attraction In the designs of modern women's fabrics - Haider Hashim Mammuod Al – Husseini (Journal of Techniques)
In the midst of the technical and artistic acceleration that we witnessed in our modern world and its development among nations and people. The artist is trying to amend the visual experiences throughout technical and behavioral artistic approaches among which is the, "abstract expressionism" - the subject of research, where abstract artist visits several trends, methods and techniques "Designer" since ancient times through his artwork to create a variety of forms, whether these forms, expressive or abstract. With regard to mixing, loss, complacency or rejection. The designer tries to answer the following questions of: whether abstract expressionism in the design of modern women’s fabrics achieves attraction. A goal is found in the search for modern women's elegance. The research objectively identified the designs of modern women's fabrics (picnic) that implemented in the style of abstract expressionism. It also spots for fabrics designs in the local markets in Baghdad which have different countries of origin (Turkey and the Republic of China) for the time period 2018 - 2019. Terminology (abstract expressionism, visual tour) was defined theoretically. As in the third chapter of the descriptive approach (content annexation), the research community included a variety of 19 models for the design of modern women's fabrics (for a picnic) The researcher excluded three models from the repetition of the design idea in different colors. Four design models were chosen intentionally and 25% of the total current research community. It was selected according to the research objectives. The research came out in the fourth chapter with the most important results where the design forms were divided between an abstract form to represent the real dimension of moving the vocabulary of the design idea. Among the models include abstract expressive vocabulary (non-form), which are aesthetic values ​​and worked to enhance the visual between the sides of the communicative equation (cloth and recipients). The conclusions included: two most common designs rely on pluralism in the formations to cling to the experience, and modify your style of work, and configurations for your staff in the design and qualification in the design and qualification on the one hand and promote attractions and the right to search recommendations and a list of sources